The level of interferons ? and ? in the blood of patients with uveitis of different clinical characteristic and course of the disease (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Social importance of uveitis is determined by high frequency of occurrence, affection of persons mainly of work ability age, high frequency of disability due to vision.Objective. To determine the peculiarity of interferons ? and ? expressions in the blood of patients with uveitis of different clinical characteristic and course of the pathological process.Materials and methods. There were examined 61 patients with uveitis of different localization (anterior and posterior), clinical course (chronic and acute), degree of severity (severe and moderate) and differential diagnosis (iridocyclitis, focal and disseminated chorioretinitis, neuritis, panuveitis) who were examined ophthalmoscopically (ophthalmoscopy, tonometry, visometry). 59 people were determined the level of interferons ? and ? in the blood plasma by the method of the immune enzyme analysis. Results. There was determined peculiarity of interferons ? and ? expressions in the blood of patients with uveitis of different clinical characteristic and course peculiarities of the pathological process. It is shown that the content of these cytokines are significantly lower in posterior uveitis as well as in the chronic course with high degree of reliability. There was found a reliable correlation between the level of interferons under the study and above mentioned characteristics. The degree of uveitis severity does not correlate with the level of interferons in the patients’ blood as well as there was no revealed association between the average values of concentration of interferons ? and ? in the blood of the patients with uveitis taking into account the differential diagnosis.Conclusions. The data obtained prove the role of interferons ? and ? in development of uveitis and may be of interest for determining the character of the course of the pathological process and treatment efficacy.
Keywords: uveitis; clinical characteristic; course; interferons ? and ?; blood plasma